Changes in P forms and fractions due to the addition of stover and biochar to growing crops in soils amended with stover and its biochar - Li, Xue; Li, Na; Yang, Jin-Feng; Xiang, Yan-Sen; Wang, Xin; Han, Xiao-Ri (Frontiers in Soil Science, 2023)
To comprehend soil P transformation and crop P uptake, it is necessary to understand how the long-term substitution of mineral fertilizers with stover or biochar affects soil properties and P forms. However, the effects of large-scale continuous stover or biochar application on soil P forms and fractions and the response of P uptake by corn are largely unknown. The purpose of this study was to investigate the role of stover and its biochar in the variation of P forms and Hedley-P fractions. A five-year field experiment in brown soil was carried out using the following treatments: non-fertilizer (CK), chemical fertilizer (NPK), chemical fertilizer + corn stover (SNPK), and chemical fertilizer + biochar (CNPK). The greatest increases in P uptake occurred during the CNPK treatment, specifically orthophosphate and Resin-P, and coincided with increases in total inorganic P and Hedley-P fractions. On the other hand, total organic P accumulation was found to be highest in the SNPK treatment, as was total inositol hexakisphosphate and orthophosphate diester accumulation. Treatments with SNPK and CNPK significantly increased adenosine monophosphate and DNA. However, no difference was found between NaHCO3-Pi and NaOH-Pi of the NPK, SNPK, and CNPK treatments. Decreasing chemical fertilizer and partially replacing it with biochar in brown soil may increase crop P uptake by degrading applied organic P forms and multiplying inorganic P forms.